2020
DOI: 10.55175/cdk.v47i8.782
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan ASI Eksklusif dan Enuresis Primer pada Anak

Abstract: <p>Enuresis adalah keluarnya air kemih yang tidak disadari dan berulang pada anak berusia 5 tahun atau lebih yang diharapkan sudah dapat mengendalikan proses berkemihnya. Istilah enuresis primer dipakai untuk anak yang belum pernah berhenti mengompol sejak bayi. Salah satu penyebab enuresis primer adalah keterlambatan maturasi sistem saraf pusat. ASI merupakan nutrisi yang ideal untuk bagi perkembangan sistem saraf. Pemberian ASI eksklusif menunjukkan manfaat besar dalam perkembangan visual, kognitif, da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…Research has indicated that during the initial phases of fungal infection, the enzymatic degradation byproducts of the cuticle serve as the intrinsic cellular signal recognized by the plant, acting as the initial elicitor of a defensive reaction (Serrano et al, 2014). A. sinensis trees often form a glue of wood fiber and resin to effectively segment damage and infection (Hasibuan et al, 2013). Therefore, the diversity of endophytic fungi decreased after agarwood formation in Qi-Nan agarwood.…”
Section: Endophytic Fungi Promoting the Formation Of Qi-nan Agarwoodmentioning
confidence: 99%
“…Research has indicated that during the initial phases of fungal infection, the enzymatic degradation byproducts of the cuticle serve as the intrinsic cellular signal recognized by the plant, acting as the initial elicitor of a defensive reaction (Serrano et al, 2014). A. sinensis trees often form a glue of wood fiber and resin to effectively segment damage and infection (Hasibuan et al, 2013). Therefore, the diversity of endophytic fungi decreased after agarwood formation in Qi-Nan agarwood.…”
Section: Endophytic Fungi Promoting the Formation Of Qi-nan Agarwoodmentioning
confidence: 99%
“…Financial performance is the result of the realization of income and expenditure which is prepared and measured on an accrual basis (Hasibuan, 2020). Financial performance can be concluded as a picture of the financial condition of a company or the finances of an agency which can be measured in a certain way which can be in the form of realization of income and expenditure which is prepared on an accrual basis which produces a conclusion about the success of the company or agency in managing finances (Darise, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Side effects experienced by children include nausea and vomiting, loss of appetite, anorexia, pain, fatigue, bone marrow suppression (anemia, leukopenia, and thrombocytopenia), alopecia, mucositis, sleeping problems, and neurological issues. The effects of chemotherapy depend on the drug characteristics (Ruggiero, Rizzo, Catalano, Coccia, Triarico, & Attiná, 2018;Hasibuan, Lubis, Rosdiana, Nafianti, & Siregar, 2019).…”
mentioning
confidence: 99%